السياسة الخارجية لدولة الإمارات العربية المتحدة ودورها في الائتلاف الخليجي تجاه الأزمة اليمنية 2012- 2019 : دراسة تحليلية - زعابي، منى عبيد عيد
This study aims to examine the mechanism of decision making in the UAE’s foreign policy, the values and objectives that were based on it, the mechanism of its implementation which led the UAE to ally with the countries of the region in a Gulf effort to resolve the Yemeni crisis during the period from 2012 to 2019. The major objective of the study is to explore the role played by the UAE to intervene in the Yemeni crisis, its justifications and the mechanisms used. What is important is the study of the development in the region, and the role of the decision makers in foreign policy. The research and analysis aim to extrapolate the real causes and objectives behind the behavior of the regional countries and the way they look into the military intervention in Yemen. The sample of this study comes from several categories: the gulf society in general and then the decision makers in the UAE and Yemen. The analytical approach and the historical method, in addition, we made use of some statements including interviews with some prominent members of the media to reach some facts supporting the research. Based on a few old case studies the researcher was able to extract a few key points, that’s the values of the decision makers are the pillars of success for the nation, and its values that played a prominent role in seeking a solution for the Yemeni crisis and seek to uphold the rights of the people and reject violence and terrorism.